2021
DOI: 10.18632/aging.202934
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived xenograft: a developing tool for screening biomarkers and potential therapeutic targets for human esophageal cancers

Abstract: Esophageal cancer (EC) represents a human malignancy, diagnosed often at the advanced stage of cancer and resulting in high morbidity and mortality. The development of precision medicine allows for the identification of more personalized therapeutic strategies to improve cancer treatment. By implanting primary cancer tissues into immunodeficient mice for expansion, patient-derived xenograft (PDX) models largely maintain similar histological and genetic representations naturally found in patients’ tumor cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 158 publications
0
6
0
Order By: Relevance
“…SHR6390 suppressed tumor cell growth in vitro and suppressed tumor growth in PDX models. [363][364][365] This kind of inhibitor suppressed RB phosphorylation and blocked the cell cycle at G1 in vivo. The combination of SHR6390 with paclitaxel or cisplatin had synergistic action in inhibiting tumor growth in vivo.…”
Section: Egfr Inhibitorsmentioning
confidence: 99%
“…SHR6390 suppressed tumor cell growth in vitro and suppressed tumor growth in PDX models. [363][364][365] This kind of inhibitor suppressed RB phosphorylation and blocked the cell cycle at G1 in vivo. The combination of SHR6390 with paclitaxel or cisplatin had synergistic action in inhibiting tumor growth in vivo.…”
Section: Egfr Inhibitorsmentioning
confidence: 99%
“…The success rate of PDX models for EC established through subcutaneous transplantation is 13.3%-55.5% [27] and is lower than that of models for other tumors [10]. Three reasons for the failure of subcutaneous PDX model establishment include lymphoproliferative lesion (LPL) replacement, absent tumor growth, and unplanned death or host infection [28].…”
Section: Construction and Optimization Of Pdx Modelsmentioning
confidence: 99%
“…To genetically inactivate IL2RG in the hamster, we employed the CRISPR/cas9 system with single guide RNAs (sgRNAs) designed to target its exon 1. Among the produced hamster lines carrying different insertions and deletions (indels) in exon 1, lines with frameshift mutations causing multiple premature stop codons in IL2RG were chosen for the establishment of IL2RG KO hamster colonies and used to produce experimental animals [ 38 , 53 ]. Lymphocyte-specific gene expression analyses in the spleen showed that IL2RG KO hamsters present severe defects in lymphocyte development which are characterized by a greatly reduced number of CD4 + T cells and barely detectable CD8 + T cells, B cells, and NK cells, mimicking many aspects of human XSCID immunodeficiency.…”
Section: Kcnq1 Tp53 and Il2rg...mentioning
confidence: 99%
“…The use of immunodeficient animals, either with IL2RG-deficiency alone or in combination with other immunodeficiencies such as RAG2-deficiency, as hosts to produce PDX models relies on their incapability of mounting immune rejections to human tissues, therefore allowing them to be xenografted in the animal hosts. Compared to in vitro cultured tumor-derived cell lines where in vitro adaptation takes place which may change the physiology of tumors, the PDX models better recapitulate the tumor biology in vivo [ 53 ]. Il2rg KO mice have been widely used as hosts for producing PDX models [ 54 ].…”
Section: Kcnq1 Tp53 and Il2rg...mentioning
confidence: 99%